Pedagogical Translanguaging and Its Application to Language Classes. (August 2022) - Cenoz, Jasone; Gorter, Durk
Pedagogical translanguaging refers to the use of different planned strategies based on activating students' resources from their whole linguistic repertoire . The aim of this article is to examine the theoretical foundations of pedagogical translanguaging and its application in the classroom. The core characteristics of pedagogical translanguaging will be discussed in relation to the languages, students and programmes. Pedagogical translanguaging embraces different practices, but they all share the characteristic of being planned by the teacher with a pedagogical purpose and using resources from the students' whole linguistic repertoire. In this way it is different from spontaneous translanguaging. Translanguaging practices aim at activating the students' multilingual and multimodal repertoires so that they can benefit from their own multilingualism. Translanguaging practices can have strong or weak forms depending on the degree of pedagogical intervention that takes place in the process of learning and the use of two or more languages in the same class session. Some strong translanguaging practices use resources from different languages in the same class so as to develop metalinguistic awareness, while other weaker forms are based on the cross-linguistic coordination of activities carried out in different classes. The article will also discuss the challenges that the implementation of pedagogical translanguaging poses for language teachers.